Quantifying dietary vitamin K and its link to cardiovascular health: a narrative review. Issue 4 (25th March 2020) - Palmer, Claire R.; Blekkenhorst, Lauren C.; Lewis, Joshua R.; Ward, Natalie C.; Schultz, Carl J.; Hodgson, Jonathan M.; Croft, Kevin D.; Sim, Marc
Abstract : Potential beneficial pathways by which vitamin K may reduce the risk of cardiovascular disease mortality. Abstract : Cardiovascular disease is the leading cause of death and disability worldwide. Recent work suggests a link between vitamin K insufficiency and deficiency with vascular calcification, a marker of advanced atherosclerosis. Vitamin K refers to a group of fat-soluble vitamins important for blood coagulation, reducing inflammation, regulating blood calcium metabolism, as well as bone metabolism, all of which may play a role in promoting cardiovascular health. Presently, there is a lack of a comprehensive vitamin K database on individual foods, which are required to accurately calculate vitamin K1 and K2 intake for examination in epidemiological studies. This has likely contributed to ambiguity regarding the recommended daily intake of vitamin K, including whether vitamin K1 and K2 may have separate, partly overlapping functions. This review will discuss the presence of: (i) vitamin K1 and K2 in the diet; (ii) the methods of quantitating vitamin K compounds in foods; and (iii) provide an overview of the evidence for the cardiovascular health benefits of vitamin K in observational and clinical trials.